Validating laboratory predictions of soil rewetting respiration pulses using field data - X. Li; X. Li; M. Pallandt; M. Pallandt; D. Naidu; D. Naidu; J. Rousk; G. Hugelius; G. Hugelius; S. Manzoni; S. Manzoni (Biogeosciences)
Improved understanding of the mechanisms driving heterotrophic CO2 emissions after rewetting of a dry soil may improve projections of future soil carbon fate. While drying and rewetting (DRW) under laboratory conditions have demonstrated that heterotrophic CO2 emissions depend on DRW features and soil and environmental conditions, these laboratory insights have not been validated in field conditions. To this aim, we collated mean respiration rates over 48 h after rewetting from two data sources: 37 laboratory studies reporting data for more than 3 DRW cycles (laboratory respiration, LR) and 6 field datasets recording hourly heterotrophic respiration and soil moisture (field respiration, FR). LR and FR were explained by six predictors using random forest algorithms and partial dependence plots. Results indicated that the most important drivers of LR and FR were SOC and temperature, respectively. Both LR and FR increased with increasing SOC and temperature. LR increased with soil dryness before rewetting, but this trend was less clear in FR. LR decreased with soil moisture increments at rewetting, while FR increased with soil moisture increments. LR was higher in soils from humid climates than from arid climates, but this effect was not observed in FR. We concluded that laboratory insights could be partly validated with current datasets. Caution should be taken when extending laboratory insights for predicting fluxes in ecosystems.